Synthesis, Characterization and Antibacterial Evaluation of Some Coumarin Derivatives - Tariq T. Abduljabbar; Mohammed K. Hadi (College of Pharmacy University of Baghdad, 2021)
Coumarin derivatives have shown different biological activities, such as antifungal, antibacterial   antiinflammatory, and antioxidant activities, besides antibiotic resistance modulating effects, and anti-HIV, hepatoprotective, and antitumor effect. So, new coumarin derivatives (hydrazones and an amide) were synthesized through multisteps reactions. All the synthesized target compounds were characterized by FT-IR spectroscopy, 1HNMR analysis. The compounds then evaluated for their anti-bacterial activity by means of well-diffusion method against two gram-positive bacteria (Staphylococcus aureus, Streptococcus pneumoniae) and two gram-negative bacteria  (E.coli and Pseudomonas aeruginosa). The highest activity was demonstrate by compound k2 which found to be highly active against pseudomonas aeruginosa.